2017
DOI: 10.1371/journal.pone.0172592
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TGF-β pathway by pirfenidone decreases extracellular matrix deposition in ocular fibroblasts in vitro

Abstract: In glaucoma surgery, fibrotic processes occur, leading to impairment of liquid outflow. Activated fibroblasts are responsible for postoperative scarring. The transforming growth factor-β (TGF-β) pathway plays a key role in fibroblast function, differentiation and proliferation. The aim of this study was the characterization of the fibrotic potential of two subtypes of primary human ocular fibroblasts and the attempt to inhibit fibrotic processes specifically, without impairing cell viability. For fibrosis inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 42 publications
2
59
0
5
Order By: Relevance
“…The same applies for PFD, where in vitro studies demonstrated inhibition of cell proliferation, myofibroblast differentiation, collagen contractility, cytokine suppression, decreased collagen and fibronectin expression, and migratory ability of cardiac, renal, lung, hepatic, and ocular fibroblasts [31,32,62–66]. An antifibrotic effect in vivo has also been described in a trabeculectomy model in rabbits, where postoperative application of PFD was associated with less scarring and improved bleb survival [67] and following GDI implantation in a rabbit model [68].…”
Section: Discussionmentioning
confidence: 99%
“…The same applies for PFD, where in vitro studies demonstrated inhibition of cell proliferation, myofibroblast differentiation, collagen contractility, cytokine suppression, decreased collagen and fibronectin expression, and migratory ability of cardiac, renal, lung, hepatic, and ocular fibroblasts [31,32,62–66]. An antifibrotic effect in vivo has also been described in a trabeculectomy model in rabbits, where postoperative application of PFD was associated with less scarring and improved bleb survival [67] and following GDI implantation in a rabbit model [68].…”
Section: Discussionmentioning
confidence: 99%
“…The systems comprise in situ polymerizing drug carriers, and will be applied by minimal invasive injection systems [11]. In parallel, in-depth understanding of fibrotic processes and drug distribution mechanisms is gained through extensive in vitro and ex vivo experimentation [12][13][14]. Restoration of near and far vision in cataract patients, or as an elective procedure in presbyopes, shall be achieved through reconstruction of the enucleated capsular bag.…”
Section: Ophthalmologic Implantsmentioning
confidence: 99%
“…Increased growth factor activity not only leads to an increase in wound healing rate, but also a higher risk for scar formation. Therefore, TGF-β is one of the most potential targets for scarring intervention [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 is a major profibrotic cytokine and increased expression plays an important role in the deposition of collagen and extracellular matrix, wound healing and scar formation in the socket contracture tissue [6]. TGF-β1 is a key mediator that induce α-SMA [11,12]. Alpha-smooth muscle actin (α-SMA) may serve as a reliable marker for myofibroblast cells [12], although others considered it as not a consistent marker for contractile fibroblasts and lots of collagen [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation